Plasma leptin, insulin, and neuropeptide Y concentrations in infants. Issue 1 (21st December 2004) - Mamì, C; Manganaro, R; Saitta, G; Marseglia, L; Martino, F; Gemelli, M
Abstract : Changes in plasma leptin, insulin, and neuropeptide Y (NPY) concentrations were determined by radioimmunological methods in healthy infants. Compared with umbilical concentrations, on the 4th day of life plasma leptin and insulin were significantly decreased, and NPY was significantly increased. No correlation was observed between leptin, insulin, and NPY.